Abnormal Uterine Bleeding In Postmenopause: Diagnosis And Management - Ayala-Peralta, Félix (2016)
Postmenopausal women in the presence of abnormal uterine bleeding spontaneously and unexpectedly requires rigorous evaluation to determine the source of the bleeding. The most common cause of postmenopausal bleeding is endometrial atrophy and endometrial polyp; however, must be ruled endometrial cancer is the cause in about 10 percent of patients. The gold standard for evaluating the endometrium is transvaginal ultrasonography and endometrial biopsy, which are two key components that help reach an accurate diagnosis.